2020
DOI: 10.3390/foods9080976
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plating, Ingredients, and Cooking Processes on the Acceptance and Authenticity of Ethnic Rice Dishes

Abstract: Familiarity and ethnic authenticity have a significant influence on the liking of ethnic food. Thus, it is crucial to identify the degree to which a dish can be modified in order to increase hedonic responses and familiarity without the loss of ethnic authenticity. This study determined the degree to which perceptions of the Korean rice dish, bibimbap, would vary upon modification of its ingredients, cooking process, or plating using the Southeast Asian market as a model system. The dish was prepared in Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…In addition, tourists who have visited more than once or have lived in the city prefer food socialized as local food. It contradicts the previous studies that found that local food choice in ASEAN is influenced by familiarity with local food (Lee et al, 2020;Mohiuddin & Al Azad, 2019;Park, Kim & Yeoman, 2019). Tourists who are familiar with the city usually choose food socialized as local food.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In addition, tourists who have visited more than once or have lived in the city prefer food socialized as local food. It contradicts the previous studies that found that local food choice in ASEAN is influenced by familiarity with local food (Lee et al, 2020;Mohiuddin & Al Azad, 2019;Park, Kim & Yeoman, 2019). Tourists who are familiar with the city usually choose food socialized as local food.…”
Section: Discussioncontrasting
confidence: 62%
“…Food was one of the major attractions for international tourists (Himanshu, 2015) and positively impacted tourism demands in ASEAN (Nguyen & Nguyen, 2021). A taste of the diversity and authenticity of the culture in Asia and ASEAN was experienced through food (Lee et al, 2020;Naruetharadhol & Gebsombut, 2020;Park, Kim, & Yeoman, 2019). The cuisine was featured in ASEAN's cultural education, awareness, and literacy initiatives (Kheng-Lian, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lee et al (2020) and Ha (2019) also revealed that ingredients, cooking process, and food presentation significantly influence customers' emotions and have composite effects on perceived ethnic authenticity. This demonstrated that restaurants should provide unique dishes with special names in their native language to emphasize authenticity and to educate customers about the history and origin of the food (Youn & Kim, 2017).…”
Section: Offering Authentic Quality Menumentioning
confidence: 98%